Caco‐2 accumulation of lutein is greater from human milk than from infant formula despite similar bioaccessibility. Issue 10 (22nd July 2014) - Lipkie, Tristan E.; Banavara, Dattatreya; Shah, Bhavini; Morrow, Ardythe L.; McMahon, Robert J.; Jouni, Zeina E.; Ferruzzi, Mario G.
<x xml:space="preserve">Abstract</x> Scope Clinical evidence suggests that the bioavailability of lutein is lower from infant formula than from human milk. The purpose of this study was to assess characteristics of human milk and lutein‐fortified infant formula that may impact carotenoid delivery. Methods and results Carotenoid bioaccessibility and intestinal absorption were modeled by in vitro digestion coupled with Caco‐2 human intestinal cell culture. Twelve human milk samples were assessed from 1–6 months postpartum, and 10 lutein‐fortified infant formula samples from three lutein sources in both ready‐to‐use and reconstituted powder forms. The relative bioaccessibility of lutein was not different (p > 0.05) between human milk (29 ± 2%) and infant formula (36 ± 4%). However, lutein delivery was 4.5 times greater from human milk than infant formula when including Caco‐2 accumulation efficiency. Caco‐2 accumulation of lutein was increasingly efficient with decreasing concentration of lutein from milk. Carotenoid bioaccessibility and Caco‐2 accumulation were not affected by lactation stage, total lipid content, lutein source, or form of infant formula (powder vs. liquid). Conclusion These data suggest that the bioavailability of carotenoids is greater from human milk than infant formula primarily due to intestinal absorptive processes, and that absorption of lutein is potentiated by factors from human milk especially at low lutein concentration.